Effect of Materials in Life Cycle Energy Assessment: A Case Study of a Single Storey Building - Sivapragasam, C.; Meyyappan, P. L.; Christy, Rithu; Akila Reddy, V.; Karthiga, S. (Asian Journal of Engineering and Applied Technology, 2019)
Life Cycle Energy Assessment (LCEA) of buildings is commonly being adopted as a tool to evaluate the environmental effects of a building throughout its entire life cycle to enhance the building sustainability. The different phases in the LCEA of a building involve the extraction & manufacturing of building materials, construction, operation, maintenance and demolishing. It measures all inputs to a building and all outputs (emissions) released to the environment in all the phases. This study particularly focuses on the ‘operational’ phase of the LCEA and recommends what materials changes in some of the building components under Indian conditions can lead to lower energy consumption. The case study considered is a single storey building with a plan dimension of 10m x 7m. eQuest software is used for energy simulation. An attempt is also made to study the influence of environmental impacts of the building key assembly components such as roofs and infill walls etc. It is strongly recommended that all structural designs should consider LCEA before it is approved.